Environment-friendly ceramic and preparation method thereof

Through the multi-stage sintering process of materials such as kaolin, the problem of poor wear resistance of ceramics is solved, and ceramics with high mechanical strength and corrosion resistance are prepared to meet the high performance requirements of various application environments.

CN119143473AInactive Publication Date: 2024-12-17福建省德化县瑜美陶瓷有限公司

Patent Information

Application Number
CN202411648375.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The wear resistance of existing ceramics is poor, and it is difficult to meet the requirements of high strength and corrosion resistance, which limits its use in various application environments.

Method used

Using grinding and mixing materials such as kaolin, boron oxide, carbon powder, zirconium, barium carbonate, calcium carbonate, boron, silicon, titanium, etc., combined with the use of zinc nitrate and dispersant, it is processed under different temperature and atmosphere conditions through a multi-stage sintering process. , ceramics with high mechanical strength, wear resistance and corrosion resistance were prepared.

Benefits of technology

The prepared ceramics have significantly improved mechanical strength, wear resistance and corrosion resistance, and can be more widely used in a variety of usage environments to meet high performance needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an environment-friendly ceramic and a preparation method thereof, and belongs to the field of ceramics, the method comprises the following steps: grinding and mixing kaolin, boric oxide, carbon powder, zirconium, barium carbonate, calcium carbonate, boron, silicon and titanium to obtain a mixture; mixing zinc nitrate, zirconium nitrate and a dispersing agent to obtain a mixed solution; mixing the mixture with the mixed liquid to obtain mixed slurry; preparing the mixed slurry into a blank body; putting the blank body into a sintering furnace, heating to 560-720 DEG C, and treating in a first treatment environment for 1.5-4 hours; the temperature of the sintering furnace is increased to 880-1130 DEG C, and treatment is conducted for 2-5 h in a second treatment environment; the temperature of the sintering furnace is increased to 1280-1420 DEG C, and treatment is conducted for 3-6 h in a third treatment environment; the temperature of the sintering furnace is increased to 1530-1620 DEG C, and treatment is conducted for 1-3 h in a fourth treatment environment; the first treatment environment, the second treatment environment, the third treatment environment and the fourth treatment environment comprise vacuum or inert atmosphere. The sintered ceramic is high in strength and good in wear resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ceramics, and in particular relates to an environmentally friendly ceramic and a preparation method thereof. Background Art

[0002] Ceramics have a long history of development. Early ceramics were mainly fired from clay and other materials. The prepared ceramics were mainly used as food utensils, wine vessels, ceramic art, etc. With the development of new materials and material processes, the raw materials and firing processes for the preparation of ceramics are constantly changing, making the performance of fired ceramics better and better, making the application fields of ceramics wider and wider, such as machinery, chemical industry, aerospace, etc., and at the same time, the performance requirements for ceramics are getting higher and higher. In many application fields, ceramics are required to have higher strength, higher wear resistance and corrosion resistance in order to be suitable for different use environment conditions. The wear resistance of existing ceramics is not good, and it is difficult to meet the use requirements, which affects the application of ceramics. Summary of the invention

[0003] The invention provides an environmentally friendly ceramic and a preparation method thereof, which are used to solve the problem of poor wear resistance of the ceramic.

[0004] The present invention provides a method for preparing an environmentally friendly ceramic, comprising: Step S1: grinding and mixing kaolin, boron oxide, carbon powder, zirconium, barium carbonate, calcium carbonate, boron, silicon and titanium to obtain a mixture; mixing zinc nitrate, zirconium nitrate and a dispersant to obtain a mixed solution; Then, the mixed material and the mixed liquid are mixed to obtain a mixed slurry; Step S2: preparing the mixed slurry into a green body to be sintered; Step S3: placing the embryo body in a sintering furnace and heating it to a first temperature of 560-720° C. in a first treatment environment for 1.5-4 hours; Step S4: raising the temperature of the sintering furnace from the first temperature of 560-720° C. to the second temperature of 880-1130° C. and treating in the second treatment environment for 2-5 hours; Step S5: raising the temperature of the sintering furnace from the second temperature of 880-1130° C. to the third temperature of 1280-1420° C. and treating in a third treatment environment for 3-6 hours; Step S6: raising the temperature of the sintering furnace from the third temperature 1280-1420° C. to the fourth temperature 1530-1620° C. and treating in the fourth treatment environment for 1-3 hours; The first processing environment includes a vacuum or an inert atmosphere, the second processing environment includes a vacuum or an inert atmosphere, the third processing environment includes a vacuum or an inert atmosphere, and the fourth processing environment includes a vacuum or an inert atmosphere.

[0005] Furthermore, the raw materials for preparing the ceramics include: Kaolin 12-25 parts by weight; Boron oxide 2.5-4.5 parts by weight; Carbon powder 0.5-1.3 parts by weight; Zirconium 0.7-1.6 parts by weight; Barium carbonate 0.5-1.2 parts by weight; Calcium carbonate 0.4-0.9 parts by weight; Zinc nitrate 0.3-0.7 parts by weight; Zirconium nitrate 0.6-1.8 parts by weight; Boron 0.5-1.4 parts by weight; Silicon 0.4-0.8 parts by weight; Titanium 0.3-1.2 parts by weight.

[0006] Further, the first processing environment is vacuum, the second processing environment includes nitrogen and argon, the third processing environment includes nitrogen and argon, and the fourth processing environment is vacuum.

[0007] Further, the third processing environment includes nitrogen, argon, silane, methane, and boron trichloride, the volume of silane in the third processing atmosphere is 1.5-4%, the volume of methane in the third processing atmosphere is 2-5%, the volume of boron trichloride in the third processing environment is 1-3%, and the volume of nitrogen in the third processing environment is 8-15%; The fourth processing environment is vacuum.

[0008] Furthermore, the kaolin is modified kaolin, and the preparation method of the modified kaolin includes: The kaolin is placed in an acid solution for pickling; The acid-washed kaolin is placed in a calcium hydroxide solution for mixing treatment; Then drying is performed to obtain a dried product; Then the dried product is mixed with boron oxide, aluminum, carbon powder, silicon, and tungsten trioxide to obtain a mixture; The mixture was placed in vacuum and treated at 620-780°C for 0.5-1.5h; The mixture is then placed in a treatment gas and treated at 1150-1320° C. for 2-3.5 hours; Then, the modified kaolin is prepared by grinding after cooling; Process gases include nitrogen and argon.

[0009] Furthermore, the boron oxide in the mixture is 0.5-0.9% of the mass of kaolin, the aluminum in the mixture is 0.3-0.7% of the mass of kaolin, the carbon powder in the mixture is 0.7-1.2% of the mass of kaolin, the silicon in the mixture is 0.5-1% of the mass of kaolin, and the tungsten trioxide in the mixture is 0.3-0.8% of the mass of kaolin.

[0010] Further, the volume of nitrogen in the process gas is 12-25%.

[0011] Furthermore, the raw materials for preparing ceramics also include: Modified mullite, the preparation method of modified mullite includes: Place the mullite in 60-85℃ water for 1-2h; After filtering, drying is performed to obtain a filtrate; Then the filtered product is mixed with titanium boride, zirconium oxide, boron carbide and carbon powder to obtain a mixed powder; The mixed powder is placed in a vacuum and treated at 950-1160°C for 0.5-1h; Then the mixed powder is placed in a modified gas and treated at 1220-1400°C for 1-3h; Finally, the temperature is lowered and then ground to obtain modified mullite; The titanium boride in the mixed powder accounts for 0.5-1% of the mass of the mullite, the zirconium oxide in the mixed powder accounts for 0.3-0.8% of the mass of the mullite, the boron carbide in the mixed powder accounts for 0.5-1.3% of the mass of the mullite, and the carbon powder in the mixed powder accounts for 0.6-1% of the mass of the mullite; The modified gas includes nitrogen, argon and silane. The volume of nitrogen in the modified gas is 7-13%, and the volume of silane in the modified gas is 1.2-2.5%.

[0012] Furthermore, the content of the modified mullite is 6-11 parts by weight.

[0013] The environmentally friendly ceramics according to the embodiments of the present invention are prepared by the preparation method described in the above embodiments.

[0014] The preparation method of the environmentally friendly ceramic of the present invention comprises the following steps: grinding and mixing kaolin, boron oxide, carbon powder, zirconium, barium carbonate, calcium carbonate, boron, silicon and titanium to obtain a mixture; mixing zinc nitrate, zirconium nitrate and a dispersant to obtain a mixed solution; and then mixing the mixture with the mixed solution to obtain a mixed slurry; and preparing an embryo body and then sintering the embryo body by the above method. The ceramic prepared by sintering has high mechanical strength, good wear resistance and good corrosion resistance, can be applied to more use environments, and can meet use requirements. DETAILED DESCRIPTION

[0015] The technical solutions in the embodiments of the present invention will be described below in conjunction with the embodiments of the present invention. The embodiments described in the present invention are part of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] The method for preparing the environmentally friendly ceramic according to the embodiment of the present invention comprises: Step S1: grinding and mixing kaolin, boron oxide, carbon powder, zirconium, barium carbonate, calcium carbonate, boron, silicon and titanium to obtain a mixture; mixing zinc nitrate, zirconium nitrate and a dispersant to obtain a mixed solution; Then, the mixed material and the mixed liquid are mixed to obtain a mixed slurry; Step S2: preparing the mixed slurry into a green body to be sintered; Step S3: placing the embryo body in a sintering furnace and heating it to a first temperature of 560-720° C. in a first treatment environment for 1.5-4 hours; Step S4: raising the temperature of the sintering furnace from the first temperature of 560-720° C. to the second temperature of 880-1130° C. and treating in the second treatment environment for 2-5 hours; Step S5: raising the temperature of the sintering furnace from the second temperature of 880-1130° C. to the third temperature of 1280-1420° C. and treating in a third treatment environment for 3-6 hours; Step S6: raising the temperature of the sintering furnace from the third temperature 1280-1420° C. to the fourth temperature 1530-1620° C. and treating in the fourth treatment environment for 1-3 hours; The first processing environment includes a vacuum or an inert atmosphere, the second processing environment includes a vacuum or an inert atmosphere, the third processing environment includes a vacuum or an inert atmosphere, and the fourth processing environment includes a vacuum or an inert atmosphere.

[0017] Optionally, the raw materials for preparing ceramics include: Kaolin 12-25 parts by weight; Boron oxide 2.5-4.5 parts by weight; Carbon powder 0.5-1.3 parts by weight; Zirconium 0.7-1.6 parts by weight; Barium carbonate 0.5-1.2 parts by weight; Calcium carbonate 0.4-0.9 parts by weight; Zinc nitrate 0.3-0.7 parts by weight; Zirconium nitrate 0.6-1.8 parts by weight; Boron 0.5-1.4 parts by weight; Silicon 0.4-0.8 parts by weight; Titanium 0.3-1.2 parts by weight.

[0018] For example, the raw materials for preparing ceramics may include: 12 parts by weight of kaolin; 2.5 parts by weight of boron oxide; 1.3 parts by weight of carbon powder; 0.7 parts by weight of zirconium; 1.2 parts by weight of barium carbonate; 0.4 parts by weight of calcium carbonate; 0.3 parts by weight of zinc nitrate; 1.8 parts by weight of zirconium nitrate; 0.5 parts by weight of boron; 0.4 parts by weight of silicon; and 1.2 parts by weight of titanium. The amounts of specific components may be adjusted as needed.

[0019] Optionally, the first processing environment is vacuum, the second processing environment includes nitrogen and argon, the third processing environment includes nitrogen and argon, and the fourth processing environment is vacuum.

[0020] In an embodiment of the present invention, the third processing environment includes nitrogen, argon, silane, methane, and boron trichloride. The volume of silane in the third processing atmosphere is 1.5-4%, the volume of methane in the third processing atmosphere is 2-5%, the volume of boron trichloride in the third processing environment is 1-3%, and the volume of nitrogen in the third processing environment is 8-15%; the fourth processing environment is vacuum. For example, the third processing environment includes nitrogen, argon, silane, methane, and boron trichloride. The volume of silane in the third processing atmosphere is 1.5%, the volume of methane in the third processing atmosphere is 5%, the volume of boron trichloride in the third processing environment is 3%, the volume of nitrogen in the third processing environment is 8%, and the fourth processing environment is vacuum. The specific gas components and volumes can be adjusted as needed.

[0021] In some embodiments of the present invention, the kaolin may be modified kaolin, and the preparation method of the modified kaolin may include: The kaolin is placed in an acid solution for pickling; The acid-washed kaolin is placed in a calcium hydroxide solution for mixing treatment; Then drying is performed to obtain a dried product; Then the dried product is mixed with boron oxide, aluminum, carbon powder, silicon, and tungsten trioxide to obtain a mixture; The mixture was placed in vacuum and treated at 620-780°C for 0.5-1.5h; The mixture is then placed in a treatment gas and treated at 1150-1320° C. for 2-3.5 hours; Then, the modified kaolin is prepared by grinding after cooling; Process gases include nitrogen and argon.

[0022] The acidic solution may be a nitric acid solution, an oxalic acid solution, a hydrochloric acid solution, etc. The acidic solution may be a 0.3-1 mol / L nitric acid solution, for example, the acidic solution may be a 0.5 mol / L nitric acid solution. The mass content of calcium hydroxide in the calcium hydroxide solution is 5-10%, for example, the mass content of calcium hydroxide in the calcium hydroxide solution is 5%. The drying process may be carried out under a vacuum environment at 60-90°C.

[0023] Optionally, the boron oxide in the mixture is 0.5-0.9% of the mass of kaolin, the aluminum in the mixture is 0.3-0.7% of the mass of kaolin, the carbon powder in the mixture is 0.7-1.2% of the mass of kaolin, the silicon in the mixture is 0.5-1% of the mass of kaolin, and the tungsten trioxide in the mixture is 0.3-0.8% of the mass of kaolin. The volume of nitrogen in the process gas is 12-25%. For example, the boron oxide in the mixture is 0.5% of the mass of kaolin, the aluminum in the mixture is 0.7% of the mass of kaolin, the carbon powder in the mixture is 0.7% of the mass of kaolin, the silicon in the mixture is 1% of the mass of kaolin, and the tungsten trioxide in the mixture is 0.8% of the mass of kaolin. The volume of nitrogen in the process gas is 12%.

[0024] In some embodiments, the raw materials for preparing ceramics may also include: Modified mullite, the preparation method of modified mullite may include: Place the mullite in 60-85℃ water for 1-2h; After filtering, drying is performed to obtain a filtrate; during the drying process, the filtrate may be dried under a vacuum environment of 65-85°C; Then the filtered product is mixed with titanium boride, zirconium oxide, boron carbide and carbon powder to obtain a mixed powder; The mixed powder is placed in a vacuum and treated at 950-1160°C for 0.5-1h; Then the mixed powder is placed in a modified gas and treated at 1220-1400°C for 1-3h; Finally, the temperature is lowered and then ground to obtain modified mullite; The titanium boride in the mixed powder accounts for 0.5-1% of the mass of the mullite, the zirconium oxide in the mixed powder accounts for 0.3-0.8% of the mass of the mullite, the boron carbide in the mixed powder accounts for 0.5-1.3% of the mass of the mullite, and the carbon powder in the mixed powder accounts for 0.6-1% of the mass of the mullite; The modified gas includes nitrogen, argon and silane. The volume of nitrogen in the modified gas is 7-13%, and the volume of silane in the modified gas is 1.2-2.5%.

[0025] For example, mullite is placed in 75°C water for 1.5 hours, filtered and dried to obtain a filtrate; the filtrate is then mixed with titanium boride, zirconium oxide, boron carbide and carbon powder to obtain a mixed powder; the mixed powder is placed in a vacuum and treated at 950°C for 1 hour; the mixed powder is then placed in a modified gas and treated at 1220°C for 3 hours; finally, the mixture is cooled and ground to obtain modified mullite; the titanium boride in the mixed powder is 0.5% of the mass of the mullite, the zirconium oxide in the mixed powder is 0.8% of the mass of the mullite, the boron carbide in the mixed powder is 0.5% of the mass of the mullite, and the carbon powder in the mixed powder is 1% of the mass of the mullite; the modified gas includes nitrogen, argon and silane, the volume of nitrogen in the modified gas is 7%, and the volume of silane in the modified gas is 2.5%.

[0026] Optionally, the content of the modified mullite is 6-11 parts by weight. For example, the content of the modified mullite is 6, 9 or 11 parts by weight.

[0027] The environmentally friendly ceramics according to the embodiments of the present invention are prepared by the preparation method described in the above embodiments.

[0028] The present invention will be described below through some embodiments. Example 1

[0029] Ingredients include: 12 parts by weight of kaolin; 2.5 parts by weight of boron oxide; 0.5 parts by weight of carbon powder; 1.6 parts by weight of zirconium; 0.5 parts by weight of barium carbonate; 0.4 parts by weight of calcium carbonate; 0.3 parts by weight of zinc nitrate; 1.8 parts by weight of zirconium nitrate; Boron 1.4 parts by weight; Silicon 0.4 parts by weight; Titanium 1.2 parts by weight; The preparation method of environmentally friendly ceramics comprises: Step S1: grinding and mixing kaolin, boron oxide, carbon powder, zirconium, barium carbonate, calcium carbonate, boron, silicon and titanium to obtain a mixture; mixing zinc nitrate, zirconium nitrate and a dispersant to obtain a mixed solution; Then, the mixed material and the mixed liquid are mixed to obtain a mixed slurry; Step S2: preparing the mixed slurry into a green body to be sintered; Step S3: placing the embryo body in a sintering furnace and heating it to a first temperature of 560°C in a first treatment environment for 4 hours; Step S4: raising the temperature of the sintering furnace from the first temperature of 560° C. to the second temperature of 1130° C. and treating in the second treatment environment for 2 hours; Step S5: raising the temperature of the sintering furnace from the second temperature 1130° C. to the third temperature 1280° C. and treating in the third treatment environment for 6 hours; Step S6: raising the temperature of the sintering furnace from the third temperature of 1280° C. to the fourth temperature of 1530° C. and treating in the fourth treatment environment for 1 hour; The dispersant is a mixture of water and ethanol, the volume ratio of water to ethanol is 1:3, the first processing environment is vacuum, the second processing environment is vacuum, the third processing environment is vacuum, and the fourth processing environment is vacuum. Example 2

[0030] Ingredients include: 25 parts by weight of kaolin; 4.5 parts by weight of boron oxide; Carbon powder 1.3 parts by weight; Zirconium 0.7 parts by weight; 1.2 parts by weight of barium carbonate; 0.9 parts by weight of calcium carbonate; 0.7 parts by weight of zinc nitrate; 0.6 parts by weight of zirconium nitrate; 0.5 parts by weight of boron; 0.8 parts by weight of silicon; 0.3 parts by weight of titanium; The preparation method of environmentally friendly ceramics comprises: Step S1: grinding and mixing kaolin, boron oxide, carbon powder, zirconium, barium carbonate, calcium carbonate, boron, silicon and titanium to obtain a mixture; mixing zinc nitrate, zirconium nitrate and a dispersant to obtain a mixed solution; Then, the mixed material and the mixed liquid are mixed to obtain a mixed slurry; Step S2: preparing the mixed slurry into a green body to be sintered; Step S3: placing the embryo body in a sintering furnace and heating it to a first temperature of 720° C. in a first treatment environment for 1.5 hours; Step S4: raising the temperature of the sintering furnace from the first temperature of 720° C. to the second temperature of 880° C. and treating in the second treatment environment for 5 hours; Step S5: raising the temperature of the sintering furnace from the second temperature of 880° C. to the third temperature of 1420° C. and treating in the third treatment environment for 3 hours; Step S6: raising the temperature of the sintering furnace from the third temperature 1420° C. to the fourth temperature 1620° C. and treating in the fourth treatment environment for 3 hours; The dispersant is a mixture of water and ethanol, the volume ratio of water to ethanol is 1:3, the first processing environment is vacuum, the second processing environment is vacuum, the third processing environment is vacuum, and the fourth processing environment is vacuum. Example 3

[0031] Ingredients include: 18 parts by weight of kaolin; 3.5 parts by weight of boron oxide; Carbon powder 0.9 parts by weight; Zirconium 1.2 parts by weight; 0.8 parts by weight of barium carbonate; 0.7 parts by weight of calcium carbonate; 0.5 parts by weight of zinc nitrate; 1.2 parts by weight of zirconium nitrate; Boron 0.9 parts by weight; Silicon 0.6 parts by weight; Titanium 0.7 parts by weight; The preparation method of environmentally friendly ceramics comprises: Step S1: grinding and mixing kaolin, boron oxide, carbon powder, zirconium, barium carbonate, calcium carbonate, boron, silicon and titanium to obtain a mixture; mixing zinc nitrate, zirconium nitrate and a dispersant to obtain a mixed solution; Then, the mixed material and the mixed liquid are mixed to obtain a mixed slurry; Step S2: preparing the mixed slurry into a green body to be sintered; Step S3: placing the embryo body in a sintering furnace and heating it to a first temperature of 620° C. in a first treatment environment for 3 hours; Step S4: raising the temperature of the sintering furnace from the first temperature of 620° C. to the second temperature of 1020° C. and treating in the second treatment environment for 3 hours; Step S5: raising the temperature of the sintering furnace from the second temperature 1020° C. to the third temperature 1350° C. and treating in the third treatment environment for 4 hours; Step S6: raising the temperature of the sintering furnace from the third temperature of 1350° C. to the fourth temperature of 1580° C. and treating in the fourth treatment environment for 2 hours; The dispersant is a mixture of water and ethanol, the volume ratio of water to ethanol is 1:3, the first processing environment is vacuum, the second processing environment is vacuum, the third processing environment is vacuum, and the fourth processing environment is vacuum. Example 4

[0032] The difference between Example 4 and Example 3 is that: The third processing environment includes nitrogen, argon, silane, methane, and boron trichloride. The volume of silane in the third processing atmosphere is 1.5%, the volume of methane in the third processing atmosphere is 5%, the volume of boron trichloride in the third processing environment is 1%, and the volume of nitrogen in the third processing environment is 8%; the fourth processing environment is vacuum. Example 5

[0033] The difference between Example 5 and Example 3 is that: The third processing environment includes nitrogen, argon, silane, methane, and boron trichloride. The volume of silane in the third processing atmosphere is 4%, the volume of methane in the third processing atmosphere is 2%, the volume of boron trichloride in the third processing environment is 3%, and the volume of nitrogen in the third processing environment is 15%. The fourth processing environment is vacuum. Example 6

[0034] The difference between Example 6 and Example 3 is that: The kaolin is modified kaolin, and the preparation method of the modified kaolin includes: The kaolin is placed in an acid solution for pickling; the acid solution is a 0.5 mol / L nitric acid solution; The acid-washed kaolin is placed in a calcium hydroxide solution for mixing; the mass concentration of calcium hydroxide in the calcium hydroxide solution is 5%; Then drying at 60°C to obtain a dried product; Then the dried product is mixed with boron oxide, aluminum, carbon powder, silicon, and tungsten trioxide to obtain a mixture; The mixture was placed in vacuum and treated at 620°C for 1.5 h; The mixture was then placed in a treatment gas and treated at 1320°C for 2 h; Then, the modified kaolin is prepared by grinding after cooling; The process gas includes nitrogen and argon, and the volume of nitrogen in the process gas is 12%; The boron oxide in the mixture is 0.5% of the mass of kaolin, the aluminum in the mixture is 0.7% of the mass of kaolin, the carbon powder in the mixture is 0.7% of the mass of kaolin, the silicon in the mixture is 1% of the mass of kaolin, and the tungsten trioxide in the mixture is 0.3% of the mass of kaolin. Example 7

[0035] The difference between Example 7 and Example 3 is that: The kaolin is modified kaolin, and the preparation method of the modified kaolin includes: The kaolin is placed in an acid solution for pickling; the acid solution is a 0.8 mol / L nitric acid solution; The acid-washed kaolin is placed in a calcium hydroxide solution for mixing; the mass concentration of calcium hydroxide in the calcium hydroxide solution is 7%; Then drying at 80°C to obtain a dried product; Then the dried product is mixed with boron oxide, aluminum, carbon powder, silicon, and tungsten trioxide to obtain a mixture; The mixture was placed in vacuum and treated at 780°C for 0.5 h; The mixture was then placed in a treatment gas and treated at 1150°C for 3.5h; Then, the modified kaolin is prepared by grinding after cooling; The process gas includes nitrogen and argon, and the volume of nitrogen in the process gas is 25%; The boron oxide in the mixture accounts for 0.9% of the mass of kaolin, the aluminum in the mixture accounts for 0.3% of the mass of kaolin, the carbon powder in the mixture accounts for 1.2% of the mass of kaolin, the silicon in the mixture accounts for 0.5% of the mass of kaolin, and the tungsten trioxide in the mixture accounts for 0.8% of the mass of kaolin. Example 8

[0036] The difference between Example 8 and Example 3 is that: The raw materials for preparing ceramics also include: Modified mullite, wherein the content of the modified mullite is 6 parts by weight, and the preparation method of the modified mullite comprises: Place the mullite in 60℃ water for 2h; After filtering, drying at 65°C was performed to obtain a filtrate; Then the filtered product is mixed with titanium boride, zirconium oxide, boron carbide and carbon powder to obtain a mixed powder; The mixed powder was placed in vacuum and treated at 950°C for 1 h; The mixed powder is then placed in a modified gas and treated at 1400°C for 1 h; Finally, the temperature is lowered and then ground to obtain modified mullite; The titanium boride in the mixed powder accounts for 0.5% of the mass of the mullite, the zirconium oxide in the mixed powder accounts for 0.8% of the mass of the mullite, the boron carbide in the mixed powder accounts for 1.3% of the mass of the mullite, and the carbon powder in the mixed powder accounts for 0.6% of the mass of the mullite; The modified gas includes nitrogen, argon and silane. The volume of nitrogen in the modified gas is 7%, and the volume of silane in the modified gas is 2.5%. Example 9

[0037] The difference between Example 9 and Example 3 is that: The raw materials for preparing ceramics also include: Modified mullite, wherein the content of the modified mullite is 11 parts by weight, and the preparation method of the modified mullite comprises: Place the mullite in 75℃ water for 1h; After filtering, drying at 80°C was performed to obtain a filtrate; Then the filtered product is mixed with titanium boride, zirconium oxide, boron carbide and carbon powder to obtain a mixed powder; The mixed powder was placed in a vacuum and treated at 1160°C for 0.5 h; The mixed powder is then placed in modified gas and treated at 1220°C for 3 hours; Finally, the temperature is lowered and then ground to obtain modified mullite; The titanium boride in the mixed powder is 1% of the mass of the mullite, the zirconium oxide in the mixed powder is 0.3% of the mass of the mullite, the boron carbide in the mixed powder is 0.5% of the mass of the mullite, and the carbon powder in the mixed powder is 1% of the mass of the mullite; The modified gas includes nitrogen, argon and silane. The volume of nitrogen in the modified gas is 13%, and the volume of silane in the modified gas is 1.2%. Example 10

[0038] The difference between Example 10 and Example 7 is that: The raw materials for preparing ceramics also include: Modified mullite, wherein the content of the modified mullite is 6 parts by weight, and the preparation method of the modified mullite comprises: Place the mullite in 60℃ water for 2h; After filtering, drying at 65°C was performed to obtain a filtrate; Then the filtered product is mixed with titanium boride, zirconium oxide, boron carbide and carbon powder to obtain a mixed powder; The mixed powder was placed in vacuum and treated at 950°C for 1 h; The mixed powder is then placed in a modified gas and treated at 1400°C for 1 h; Finally, the temperature is lowered and then ground to obtain modified mullite; The titanium boride in the mixed powder accounts for 0.5% of the mass of the mullite, the zirconium oxide in the mixed powder accounts for 0.8% of the mass of the mullite, the boron carbide in the mixed powder accounts for 1.3% of the mass of the mullite, and the carbon powder in the mixed powder accounts for 0.6% of the mass of the mullite; The modified gas includes nitrogen, argon and silane. The volume of nitrogen in the modified gas is 7%, and the volume of silane in the modified gas is 2.5%. Embodiment 11

[0039] The difference between Example 11 and Example 7 is that: The raw materials for preparing ceramics also include: Modified mullite, wherein the content of the modified mullite is 11 parts by weight, and the preparation method of the modified mullite comprises: Place the mullite in 75℃ water for 1h; After filtering, drying at 80°C was performed to obtain a filtrate; Then the filtered product is mixed with titanium boride, zirconium oxide, boron carbide and carbon powder to obtain a mixed powder; The mixed powder was placed in a vacuum and treated at 1160°C for 0.5 h; The mixed powder is then placed in modified gas and treated at 1220°C for 3 hours; Finally, the temperature is lowered and then ground to obtain modified mullite; The titanium boride in the mixed powder is 1% of the mass of the mullite, the zirconium oxide in the mixed powder is 0.3% of the mass of the mullite, the boron carbide in the mixed powder is 0.5% of the mass of the mullite, and the carbon powder in the mixed powder is 1% of the mass of the mullite; The modified gas includes nitrogen, argon and silane. The volume of nitrogen in the modified gas is 13%, and the volume of silane in the modified gas is 1.2%.

[0040] The ceramics prepared by the method in the above embodiment were tested, and the specific test results can be shown in Table 1.

[0041]

[0042] Corrosion resistance test of ceramics: 1. Acid resistance test: Wash the ceramic with deionized water and dry it, weigh the ceramic and observe the surface condition, soak the ceramic in a 0.6 mol / L nitric acid solution at 50°C for 150 hours, wash it with deionized water and dry it, weigh the ceramic again, and compare the changes before and after.

[0043] 2. Alkali resistance test: Wash the ceramic with deionized water and dry it, weigh the ceramic and observe the surface condition, soak the ceramic in a 0.6 mol / L sodium hydroxide solution at 50°C for 150 hours, take it out, wash it with deionized water and dry it, weigh the ceramic again, and compare the changes before and after.

[0044] By conducting an acid resistance test on the ceramics in Examples 1-11, the surface and quality of the ceramics did not change before and after the test. By conducting an alkali resistance test on the ceramics in Examples 1-11, the surface and quality of the ceramics did not change before and after the test, which shows that the ceramics in the embodiments of the present invention have good corrosion resistance.

[0045] It can be seen from the test results that the ceramics prepared by the method in the above embodiments of the present invention have strong corrosion resistance, high tensile strength, good wear resistance, good durability and stability, and can meet the use requirements.

[0046] Some specific embodiments of the present invention are provided above and described in detail. The protection scope of the present invention is not limited to the above specific embodiments. Improvements made by those skilled in the art based on common knowledge or conventional techniques also fall within the protection scope of the present invention.

Claims

1. A method for preparing environmentally friendly ceramics, characterized in that: include: Step S1: grinding and mixing kaolin, boron oxide, carbon powder, zirconium, barium carbonate, calcium carbonate, boron, silicon and titanium to obtain a mixture; mixing zinc nitrate, zirconium nitrate and a dispersant to obtain a mixed solution; Then, the mixed material is mixed with the mixed liquid to obtain a mixed slurry; Step S2: preparing the mixed slurry into a green body to be sintered; Step S3: placing the embryo body in a sintering furnace and heating it to a first temperature of 560-720° C. in a first treatment environment for 1.5-4 hours; Step S4: raising the temperature of the sintering furnace from the first temperature of 560-720° C. to the second temperature of 880-1130° C. and treating in the second treatment environment for 2-5 hours; Step S5: raising the temperature of the sintering furnace from the second temperature of 880-1130° C. to the third temperature of 1280-1420° C. and treating in a third treatment environment for 3-6 hours; Step S6: raising the temperature of the sintering furnace from the third temperature 1280-1420° C. to the fourth temperature 1530-1620° C. and treating in the fourth treatment environment for 1-3 hours; The first processing environment includes a vacuum or an inert atmosphere, the second processing environment includes a vacuum or an inert atmosphere, the third processing environment includes a vacuum or an inert atmosphere, and the fourth processing environment includes a vacuum or an inert atmosphere.

2. The preparation method according to claim 1, characterized in that: The raw materials for preparing ceramics include: 12-25 parts by weight of kaolin; 2.5-4.5 parts by weight of boron oxide; Carbon powder 0.5-1.3 parts by weight; Zirconium 0.7-1.6 parts by weight; Barium carbonate 0.5-1.2 parts by weight; Calcium carbonate 0.4-0.9 parts by weight; 0.3-0.7 parts by weight of zinc nitrate; 0.6-1.8 parts by weight of zirconium nitrate; Boron 0.5-1.4 parts by weight; Silicon 0.4-0.8 parts by weight; Titanium 0.3-1.2 parts by weight.

3. The preparation method according to claim 1 or 2, characterized in that: The first processing environment is vacuum, the second processing environment includes nitrogen and argon, the third processing environment includes nitrogen and argon, and the fourth processing environment is vacuum.

4. The preparation method according to claim 1 or 2, characterized in that: The third processing environment includes nitrogen, argon, silane, methane, and boron trichloride, wherein the volume of silane in the third processing atmosphere is 1.5-4%, the volume of methane in the third processing atmosphere is 2-5%, the volume of boron trichloride in the third processing environment is 1-3%, and the volume of nitrogen in the third processing environment is 8-15%; The fourth processing environment is vacuum.

5. The preparation method according to claim 1, characterized in that: The kaolin is modified kaolin, and the preparation method of the modified kaolin includes: The kaolin is placed in an acid solution for pickling; The acid-washed kaolin is placed in a calcium hydroxide solution for mixing treatment; Then drying is performed to obtain a dried product; Then, the dried product is mixed with boron oxide, aluminum, carbon powder, silicon, and tungsten trioxide to obtain a mixture; The mixture is placed in vacuum and treated at 620-780° C. for 0.5-1.5 h; The mixture is then placed in a treatment gas and treated at 1150-1320° C. for 2-3.5 hours; Then, the modified kaolin is prepared by grinding after cooling; The process gas includes nitrogen and argon.

6. The preparation method according to claim 5, characterized in that: The boron oxide in the mixture accounts for 0.5-0.9% of the mass of kaolin, the aluminum in the mixture accounts for 0.3-0.7% of the mass of kaolin, the carbon powder in the mixture accounts for 0.7-1.2% of the mass of kaolin, the silicon in the mixture accounts for 0.5-1% of the mass of kaolin, and the tungsten trioxide in the mixture accounts for 0.3-0.8% of the mass of kaolin.

7. The preparation method according to claim 5, characterized in that: The volume of nitrogen in the process gas is 12-25%.

8. The preparation method according to claim 1 or 5, characterized in that: The raw materials for preparing ceramics also include: Modified mullite, the preparation method of the modified mullite comprises: Place the mullite in 60-85℃ water for 1-2h; After filtering, drying is performed to obtain a filtrate; Then, the filtered material is mixed with titanium boride, zirconium oxide, boron carbide and carbon powder to obtain a mixed powder; The mixed powder is placed in a vacuum and treated at 950-1160° C. for 0.5-1 h; Then, the mixed powder is placed in a modified gas and treated at 1220-1400° C. for 1-3 hours; Finally, the temperature is lowered and then ground to obtain modified mullite; The titanium boride in the mixed powder accounts for 0.5-1% of the mass of the mullite, the zirconium oxide in the mixed powder accounts for 0.3-0.8% of the mass of the mullite, the boron carbide in the mixed powder accounts for 0.5-1.3% of the mass of the mullite, and the carbon powder in the mixed powder accounts for 0.6-1% of the mass of the mullite; The modified gas includes nitrogen, argon and silane. The volume of nitrogen in the modified gas is 7-13%, and the volume of silane in the modified gas is 1.2-2.5%.

9. The preparation method according to claim 8, characterized in that: The content of the modified mullite is 6-11 parts by weight.

10. An environmentally friendly ceramic, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Straw-containing external wall insulating brick and preparation method thereof

    CN109133979A

  • High-strength wear-resistant refractory castable and preparation method thereof

    CN109305820A

  • Preparation method of honeycomb-shaped wear-resistant ceramic block

    CN112500146A

  • High-performance ceramic sagger and preparation method thereof

    CN116924785A

  • Preparation method of environment-friendly ceramic and ceramic

    CN118084468A

Cited By

  • Novel antibacterial environment-friendly ceramic and preparation method thereof

    CN120504534A

  • Environment-friendly ceramic and preparation method thereof

    CN120518382A